2016
DOI: 10.1002/jbt.21867
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective role of vardenafil against experimentally induced hepatitis in mice

Abstract: Vardenafil is a selective phosphodiesterase-5 inhibitor used for erectile dysfunction treatment. The hepatoprotective role of vardenafil against acute hepatitis is not reported yet. Hence, this study aims to explore the protective role of vardenafil against concanavalin A (Con A) induced acute liver injury. Mice were pretreated with vardenafil (0.17 mg/kg/day) for seven consecutive days, and then subjected to a single IV injection of Con A. The results demonstrated that the vardenafil pretreatment significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 38 publications
3
4
0
Order By: Relevance
“…Our data showed that LCA induced the activation of NF-κB and markedly increased the release of inflammatory cytokines, and these effects were greatly reduced by vardenafil treatment. These findings are consistent with previous investigations that showed the ability of vardenafil to suppress NF-κB activation and subsequently the release of inflammatory cytokines in autoimmune hepatitis [17] and lung inflammation [42].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our data showed that LCA induced the activation of NF-κB and markedly increased the release of inflammatory cytokines, and these effects were greatly reduced by vardenafil treatment. These findings are consistent with previous investigations that showed the ability of vardenafil to suppress NF-κB activation and subsequently the release of inflammatory cytokines in autoimmune hepatitis [17] and lung inflammation [42].…”
Section: Discussionsupporting
confidence: 82%
“…This observation is consistent with previous studies that reported the hepatoprotective effects of PDE-5 inhibitors against ischemic liver injury [15], fatty liver [22], and hepatic fibrosis [14]. Furthermore, our lab recently demonstrated the protective effects of vardenafil against autoimmune hepatitis [17].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The Con A was dissolved in normal saline (Sigma-Aldrich, St. Louis, MO, USA) and was used to induce AIH via one intravenous dose (15 mg/kg) as described previously [8,25]. The mice were assigned to five groups (eight mice each) and received the treatment as follows:…”
Section: Induction Of Aih and Experimental Groupsmentioning
confidence: 99%
“…A convenient animal model that resembles AIH in humans has been well established using a single dose of concanavalin A (Con A) which is a lectin derived from the Canavalia ensiformis extract [8]. Con A-induced hepatitis has a ubiquitous role and specificity in the activation of direct T-cells.…”
Section: Introductionmentioning
confidence: 99%